An update on anti-NMDA receptor encephalitis for neurologists and psychiatrists: mechanisms and models. Issue 11 (November 2019) - Dalmau, Josep; Armangué, Thais; Planagumà, Jesús; Radosevic, Marija; Mannara, Francesco; Leypoldt, Frank; Geis, Christian; Lancaster, Eric; Titulaer, Maarten J; Rosenfeld, Myrna R; Graus, Francesc
Summary: The identification of anti-NMDA receptor (NMDAR) encephalitis about 12 years ago made it possible to recognise that some patients with rapidly progressive psychiatric symptoms or cognitive impairment, seizures, abnormal movements, or coma of unknown cause, had an autoimmune disease. In this disease, autoantibodies serve as a diagnostic marker and alter NMDAR-related synaptic transmission. At symptom onset, distinguishing the disease from a primary psychiatric disorder is challenging. The severity of symptoms often requires intensive care. Other than clinical assessment, no specific prognostic biomarkers exist. The disease is more prevalent in women (with a female to male ratio of around 8:2) and about 37% of patients are younger than 18 years at presentation of the disease. Tumours, usually ovarian teratoma, and herpes simplex encephalitis are known triggers of NMDAR autoimmunity. About 80% of patients improve with immunotherapy and, if needed, tumour removal, but the recovery is slow. Animal models have started to reveal the complexity of the underlying pathogenic mechanisms and will lead to novel treatments beyond immunotherapy. Future studies should aim at identifying prognostic biomarkers and treatments that accelerate recovery.